Experimental testing of the new flow equation of cement dispersion - Szerafin, Jerzy (Budownictwo i Architektura / Civil and Architectural Engineering, 2009)
The new flow equation of cement dispersion included factor of the friction between cement grains is presented in the paper. The analysis of the calculation’s results confirms the property of new equation. In the main part of the paper the results of experimental research were presented. The first part of research applies to cement flow through annular pipe, which exactly matches the theoretical model assumptions. The second part of flow tests was carried out in aggregate pile, which is typical to many practical applications of cement injection. Calculation and experimental test’s results are compatible and proof the correctness of new flow equations.